DEVELOPMENT OF LEARNING CYCLE MATHEMATICS TEACHING MATERIALS CONTAINING P5 TO IMPROVE STUDENTS' CRITICAL-CREATIVE SKILLS - Nurwalidainismawati Nurwalidainismawati; Nurlailatun Ramdani; Uswatun Hasanah; Firdaus Firdaus (Program Studi PGSD Universitas Flores, 2025)
Critical and creative thinking skills in mathematics are essential competencies. However, many students still have difficulty understanding mathematical concepts because the learning approach is still conventional. The purpose of this study is to develop contextual and enjoyable mathematics teaching materials to improve students' critical and creative thinking skills through numeracy activities. In addition, the integration of the P5-based learning cycle can encourage holistic and applicable learning to real-world problems. The research method used the Borg & Gall Research and Development (R&D) model, which was modified into 8 stages. The research subjects were 60 fifth-grade students at SDN Inpres Dodirungga and Inpres Talabiu. Data collection instruments included validation sheets, response questionnaires, and tests. Data analysis used a completeness test, a mean difference test, and an N-gain test. The results showed that the pretest-posttest normality test had a Pvalue of 0.200 and 1.91 (P>0.05), and the homogeneity test had a P-value of 0.82 and 0.398 (P>0.05), indicating that the data were normally distributed and homogeneous. Meanwhile, the N-Gain scores for the control class (72.88) and the experimental class (72.73). Based on the results of the N-Gain test and the difference in means, it can be concluded that there was an increase in the pretest-posttest results of students (control-experimental), meaning that the development and use of P5-based learning cycle teaching materials had an effect on improving students' critical and creative thinking skills in elementary school.